THE PROCEDURE FOR INSTALLING SECURE AND EFFICIENT STUTTERS - Saparbaevich, Davletov Azamat (Journal of Higher Education and Academic Advancement, 2024)
This paper introduces a novel conceptualization of the chimney in a heating boiler for multi-storey residential buildings. It also examines the safety and efficiency aspects associated with the utilization of these chimneys in high-rise apartments